Determination of the Harmonic Losses in an Induction Motor Fed by an Inverter - Nasir, B. A. (Engineering, Technology & Applied Science Research, 2022)
The advancement, development, improvement, and increased use of power electronic converters led to the efficient speed control of electrical drives. The most famous three-phase induction motor-related control to Pulse-Width Modulation (PWM) technique is used to operate multilevel inverters such as variable-frequency or six-step Voltage Source Inverter (VSI). Switching devices of the inverter are used in the drive systems and act as the main source of harmonics. When the induction motor is fed from the PWM inverter, it will be supplied by low order (5th, 7th, 11th) time harmonic voltage. The motor performance is affected by the presence of these time harmonic components because the additional losses generated in the motor defect its performance, generate pulsating torque, and reduce efficiency. In this work, the analysis of a dynamic model of an induction motor in transient and steady-state operation is developed, considering the effect of time-harmonic voltages generated by the inverter, skin effect, skew effect, temperature rise effect, iron core loss, stray load loss, and magnetic saturation on the motor performance. The performance of the motor is studied by the time-harmonic equivalent circuit and by the fundamental equivalent circuit. The motor performance in terms of efficiency and power factor is compared with the experimental results for both sinusoidal and VSI motor feeds in order to validate the model accuracy.